EFFECTS OF TOPICAL TOMATO (LYCOPERSICON LYCOPERSICUM L) EXTRACT ON MALONDYALDEHYDE LEVEL AND THE NUMBER OF MELANIN IN SKIN CAUSED BY ULTRAVIOLET-B RADIATION - Djajadihardja, Andreas Yudi Prasetyo; Nasihun, Taufiqurrachman; Hussaana, Atina (Faculty of Medicine, Universitas Islam Sultan Agung (UNISSULA), Indonesia, 2019)
INTRODUCTION: UVB radiation on skin may increase reactive oxygen species (ROS) level and cause hyperpigmentation. Polyphenol, an antioxidant contained in tomato, is able to quench ROS and inhibit tyrosinase activity.OBJECTIVE: This study aims to evaluate the effect of topical tomato lotion on Malondyaldehide (MDA) level and the amount of melanin in skin following UVB radiation.METHODS: In this experimental study, 28 female Balb/c mice are randomly divided into 4 groups: control group (C-G) are given with base lotion, and Lycopersicum groups 0.14 (L-014), 0.7 (L-07) and 1.4 (L-14) are given with tomato lotion of concentration of 0.14%, 0.7% and 1.4% daily, respectively. All of the mice are exposed to UVB at 1MED once every two days for two weeks before lotion application. On day 16, all mice are terminated, and their skin tissues are prepared for MDA level and the amount of melanin assessment.RESULTS: The ANOVA statistical analysis shows a significant difference in the MDA level and the number of melanin of the groups, (p<0.05). The post-hoc LSD analysis shows that the level of MDA in L-14 (1.13) is significantly lower than that in L-07 (2.21), L-014 (2.47), and C-G (5.61), p<0.005. The amount of melanin in L-14 (10.00) is significantly lower than that in L-014 (23.50) and C-G (33.67), p<0.05. The amount of melanin in L-07 (13.00) is not significantly higher than that in L-14, p>0.05. The correlation between MDA level and the amount of melanin shows a strongly positive correlation value (r2) = 0.648CONCLUSION: Topical administration of tomato extract lotion significantly decreases the MDA level and the number of melanin in the mice’s skin following UVB radiation.